Internalization of Pakpak Writing Characters for Daily Disclosure - Solin, Sahala Martua (Universitas Pendidikan Indonesia, 2022)
The existence of the Pakpak language among the families and communities of Pakpak migrants from time to time is further eroded by the incomprehension of its 'writing and pronunciation.' As an initiative to defend his vision against the scour of civilization, for the sake of preserving the culture and habits of these ethnic linguistic characters, the author searches for and finds Pakpak's original writings to get character letters that explain how to express them in everyday language. This research was conducted using qualitative methods, data collection through literature study, observation, online interviews, and document analysis. The purpose of this research is to a) internalize the characters of Pakpak's writing for the love of his identity; and b) can be socialized as an alternative in the process of learning written characters and tribal languages for the sake of awakening local wisdom based on aesthetics and ethics. The results showed that strengthening the understanding of Pakpak's writing can foster the character of an individual with a personality.